Transarterial Chemoembolization Combined With Tyrosine Kinase Inhibitors for Intermediate‐Stage Hepatocellular Carcinoma, What Else Can We Do? - Deng, Jun; Wen, Feng (Frontiers in Oncology, 2022)
Transarterial chemoembolization (TACE) has been considered the standard treatment for intermediate-stage hepatocellular carcinoma(HCC). However，intermediate‐stage HCC is highly heterogeneous with a broad population with varying tumour burdens, liver function. This suggests that TACE monotherapy treatment might not be suitable for all patient with intermediate‐stage HCC. The administration of tyrosine kinase inhibitors (TKIs) has become an important treatment option for improving the prognosis of patients with advanced HCC. Over the years, Several trials have been conducted to explore the combinational effects of TACE with TKIs for intermediate-stage HCC. However，the clinical efficacy is still controversial, and its potential clinical utility needs to be confirmed. This review will focus on the recent progress of TACE combined TKIs for intermediate-stage HCC.